An Integrative Volatile Terpenoid Profiling and Transcriptomics Analysis for Gene Mining and Functional Characterization of AvBPPS and AvPS Involved in the Monoterpenoid Biosynthesis in Amomum villosum - Wang, Hong; Ma, Dongming; Yang, Jinfen; Deng, Ke; Li, Meng; Ji, Xiaoyu; Zhong, Liting; Zhao, Haiying (Frontiers in Plant Science, 2018)
Amomum villosum, also known as Fructus Amomi, has been used to treat digestive diseases such as abdominal pain, vomiting and dysentery. Volatile terpenoids are the active metabolites in the essential oil of Fructus Amomi. Nevertheless, downstream genes responsible for activing metabolites biosynthesis in A. villosum still remain unclear. Here, we report the use of an integrative volatile terpenoid profiling and transcriptomics analysis for mining the corresponding genes involved in volatile terpenoid biosynthesis. Ten terpene synthase (TPS) genes were discovered, and two of them were cloned and functionally characterized. AvTPS1 (AvPS: pinene synthase) catalyzed GPP to form α-pinene and β-pinene; AvTPS3 (AvBPPS: bornyl diphosphate synthase) produced bornyl diphosphate as major product and the other three monoterpenoids as minor products. Metabolite accumulation and gene expression pattern combined with AvPS biochemical characterization suggested that AvPS might play a role in biotic defense. On the other hand, the most active ingredient, bornyl acetate was highly accumulated in seeds and was consistent with the high expression of AvBPPS, which further indicated that AvBPPS is responsible for the biosynthesis of bornyl acetate, the final metabolite of bornyl diphosphate in A. villosum. This study can be used to improve the quality of A. villosum through metabolic engineering, and for the sustainable production of bornyl acetate in heterologous hosts.